The Development of an Action Plan for Enhancing Teachers’ Innovative Leadership Based on Organization Culture at Primary Schools in Best Educational Organization, China - Wang Lee, Wei-Chi; Ye, Yan (Journal of Roi Kaensarn Academi, 2023)
This study mainly aimed to explore the relationship between teachers’ innovative leadership and school organizational culture; examine the effect of demographic factors on teachers’ innovative leadership and school organizational culture; and to develop an action plan for better teachers’ leadership in primary schools of Best Educational Organization in China. Through systematic literature review, the researcher developed a questionnaire to survey teachers’ innovative leadership and school organizational culture. A total of 390 full-time teachers from three primary schools of Best Educational Organization in China was used as the target group. Based on the qualitative and quantitative analyses, the study developed a model and proposed an action plan and put it into the implementation for a term. Finally, the findings showed that: 1) Teachers’ perception of innovative leadership before implementing the action plan was at a moderate level in this study. 2)Teachers’ overall perception of school organizational culture was at a high level. 3). Teachers’ perceptions of innovative leadership and their perception of school organizational culture were significantly different according to their demographic factors such as age, service years, and position. 4) Teachers’ perceptions of innovative leadership were highly positively correlated with perceptions of school organizational culture. 5) Teachers’ innovative leadership after implementing the action plan was improved. Discussion based on each research objective was conducted and recommendations for the schools and teacher were provided by the end of the study.